Institutional Trust 2004 - Holmberg, Sören; Weibull, Lennart; MedieAkademin; TNS Gallup (University of Gothenburg, 2014)
Since 1997, MedieAkademin has carried out an annual survey titled The Institutional Trust. The survey has focused on major social institutions, such as the parliament, big business, the daily press, and TV/radio, as well as some specific companies such as Sveriges Television, TV4, IKEA, Skandia, and Volvo. The number of institutions included has varied somewhat over the years. Some of the institutions and companies have been measured every year while others have been investigated more irregularly.

The survey was carried out by NFO Infratest and involved 740 individuals who were interviewed by telephone between November 2 and 22, 2004. The survey comprised some 50 institutions/companies/brands. The 2004 survey also included questions about some normative demands on large corporations.

Purpose:

To study the trust that Swedish people have in social institutions, political parties, media, brands/companies, and leaders.

MedieAkademins förtroendebarometer har genomförts årligen sedan 1997. Undersökningen har varje år dels avsett ett urval viktiga samhällsinstitutioner som exempelvis riksdagen, storföretagen, dagspressen och radio-TV, dels ett antal konkreta medier, bl.a Sveriges Television och TV4, och specifika företag, som t ex IKEA, Skandia och Volvo. Antalet bedömda institutioner har varierat något mellan enskilda år. Vissa av institutionerna/medierna/företagen har mätts varje år, andra har studerats mer oregelbundet.

Undersökningen 2004 omfattade 740 intervjupersoner och genomfördes 2 - 22 november. För intervjuerna som görs per telefon har NFO Infratest (sedan 2004 TNS Gallup AB) i Göteborg svarat. I undersökningen 2004 ingår fler institutioner/företag/varumärken är tidigare, sammanlagt ett femtiotal. I studien 2004 ingår en serie frågor om olika normativa krav på storföretag.

Syfte:

Studera svenska folkets förtroende till samhällsinstitutioner, politiska partier, medier, varumärken/företag och ledare.
Förtroendebarometer 2004
Keywords: mass media; massmedia; trust; förtroende; political attitudes; politiska åsikter; trust in government; förtroende för regeringen; Media; Media; POLITICS; POLITIK; Social Sciences; Samhällsvetenskap